2021
DOI: 10.1016/j.onehlt.2021.100311
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Mycobacterium ulcerans environment to Buruli ulcer disease: Progress and challenges

Abstract: Buruli ulcer (BU), the second most common mycobacterial disease in West Africa, is a necrotizing skin disease that can lead to high morbidity in affected patients. The disease is caused by Mycobacterium ulcerans (MU), whose major virulence factor is mycolactone. Although early infection can be treated with antibiotics, an effective preventative strategy is challenging due to unknown reservoir(s) and unresolved mode(s) of transmission. Further, disease occurrence in remote locations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 96 publications
(170 reference statements)
0
13
0
Order By: Relevance
“…No human-to-human transmission of this infection has ever been reported. The ecological characteristics and mode of transmission of M. ulcerans are not entirely understood, and several fundamental questions remain unanswered [16,17]. One key concern relates to the routes by which M. ulcerans crosses the human skin barrier.…”
Section: Introductionmentioning
confidence: 99%
“…No human-to-human transmission of this infection has ever been reported. The ecological characteristics and mode of transmission of M. ulcerans are not entirely understood, and several fundamental questions remain unanswered [16,17]. One key concern relates to the routes by which M. ulcerans crosses the human skin barrier.…”
Section: Introductionmentioning
confidence: 99%
“…ulcerans underneath the skin either through mechanical injury or through insect bites as mechanical vectors may be relevant for transmission of M . ulcerans from environmental reservoirs [ 22 , 23 ]. Understanding the route of transmission is critical to protect endemic communities.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies investigated several risk factors that might facilitate the transmission of Buruli ulcer. For example, quantitative studies revealed that contact with unprotected fresh water bodies is associated with a high number of Buruli ulcer infections [ 16 , 22 , 23 , 31 ]. Stagnant and unprotected fresh water sources seem to present the highest risk [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although transmission of M. ulcerans remains poorly understood, the main identified risk factor for acquiring Buruli ulcer is living in proximity of potentially contaminated water sources. One of the probable reservoirs of M. ulcerans is linked to the aquatic environment and humans are generally contaminated through activities involving sources of water as well as water bodies and streams [1][2][3][4][5][6]. M. ulcerans produces a toxin, mycolactone, which mediates host colonization and tissue damage [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the probable reservoirs of M . ulcerans is linked to the aquatic environment and humans are generally contaminated through activities involving sources of water as well as water bodies and streams [ 1 6 ]. M .…”
Section: Introductionmentioning
confidence: 99%